Efektifitas Pemberian Tablet Tambah Darah terhadap Anemia Remaja di SMPN 1 Parongpong - Simatupang, Savely; Widiyarti, Sapti Heru (Universitas Malahayati, 2024)
ABSTRACT Anemia can affect the social and economic development of a country. Adolescent girls are a group with a ten times greater risk of developing anemia compared to adolescent boys. The government carries out a program to prevent and control anemia in young girls and women of childbearing age by administering blood supplement tablets (TTD). By administering TTD, it is hoped that the incidence of anemia will be reduced. This study aims to determine pre, post Hb levels and the effect of TTD administration on Hb levels. This research is quantitative research, with an experimental research design. The population in this study was 67 female students at SMPN 1 Parongpong. Samples were taken purposively with a total sample of 23 female students who after checking their Hb showed mild and moderate anemia. Data were collected in this study by checking Hb levels before and after administering TTD 4 times in a row for 4 weeks. The results of the study were that there was no significant difference between Hb levels before and after giving TTD to young women at SMP I Parongpong. The average Hb level before giving TTD was 10.85g/dL, and after giving TTD 10.83g/dL. The result of the t - count of this research is 0.047, while the t - table is 2.069. The result is t - count < t - table, this means that there is no significant difference. The results of this research recommend that schools pay attention to snacks sold in the school environment, provide direction for female students to maintain healthy eating patterns, and regulate good sleep patterns. Keyword: Anemia, Haemoglobin, Teenager ABSTRAK Anemia dapat mempengaruhi pembangunan sosial dan ekonomi suatu negara. Remaja putri merupakan kelompok dengan resiko sepuluh kali lebih besar untuk terjadinya anemia dibandingkan dengan remaja putra. Pemerintah melakukan Program Pencegahan dan Penanggulangan Anemia pada Remaja Putri dan Wanita Usia Subur dengan pemberian tablet tambah darah (TTD). Dengan pemberian TTD diharapkan menurunkan angka kejadian anemia. Penelitian ini bertujuan untuk mengetahui kadar Hb pre, post dan pengaruh pemberian TTD pada kadar Hb. Penelitian ini adalah penelitian kuantitatif, dengan design penelitian eksperimen. Populasi dalam penelitian ini adalah remaja putri SMPN 1 Parongpong sebanyak 67 siswi. Diambil sampel secara purposive dengan jumlah sampel 23 siswi yang setelah di cek Hb didapat hasil anemia ringan dan sedang. Pengumpulan data dalam penelitian ini dengan cara melakukan pemeriksaan kadar Hb sebelum dan sesudah pemberian TTD 4 kali berturut-turut selama 4 minggu. Hasil penelitian adalah tidak terdapat perbedaan yang signifikan antara kadar Hb sebelum dan setelah pemberian TTD pada remaja putri di SMP I Parongpong. Rata-rata kadar Hb sebelum pemberian TTD adalah 10,85g/dL, dan setelah pemberian TTD 10,83g/dL. Hasil dari t – hitung penelitian ini adalah 0.047, sedangkan t – tabel adalah 2.069. Hasilnya adalah t – hitung < t – tabel, hal ini mempunyai arti bahwa tidak terdapat perbedaan yang signifikan. Hasil penelitian ini merekomendasikan agar pihak sekolah memperhatikan jajanan yang dijual dilingkungan sekolah, memberi arahan agar siswi mengatur pola makan sehat, mengatur pola tidur yang baik. Kata Kunci: Anemia, Hemoglobin, Remaja Putri, TTD